2022
DOI: 10.1007/s11858-022-01343-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of classroom teaching practices on students’ mathematics learning interest, mathematics self-efficacy and mathematics test achievements: a secondary analysis of Shanghai data from the international video study Global Teaching InSights

Abstract: Teaching effectiveness is a core issue in educational research; however, there is little consensus about the most important results of classroom teaching from an international perspective. The effectiveness of teaching has remained a ‘black box’ for a long time. In the secondary study described in this paper we used empirical data for Shanghai taken from the international Organization for Economic Co-operation and Development (OECD) study Global Teaching InSights (GTI)—initially the Teaching and Learning Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
2
3
0
1
Order By: Relevance
“…This finding aligns with the prior research, which reported that students who perceive greater social support (from parents, teachers, and peers) display more positive attitudes toward STEM education [48]. Teachers also have been found to play a significant pedagogical function through nine different teaching strategies (Figure 5) in the classroom, training students in academic subject areas and placidly contributing to developing distinct subject interests [49]. In line with the SCCT and EVT, the findings indicate the importance of teachers and parents in fostering student interests and self-efficiency in science [50] and mathematics [49,51].…”
Section: Discussionsupporting
confidence: 87%
“…This finding aligns with the prior research, which reported that students who perceive greater social support (from parents, teachers, and peers) display more positive attitudes toward STEM education [48]. Teachers also have been found to play a significant pedagogical function through nine different teaching strategies (Figure 5) in the classroom, training students in academic subject areas and placidly contributing to developing distinct subject interests [49]. In line with the SCCT and EVT, the findings indicate the importance of teachers and parents in fostering student interests and self-efficiency in science [50] and mathematics [49,51].…”
Section: Discussionsupporting
confidence: 87%
“…These results support the concept of cooperative learning usage within classrooms (Ridwan, et al, 2021). It is seen that cooperative learning impacts positively on the academic performance of mathematics students (Zhu & Kaiser, 2022). Cooperative learning refers to small, groupbased instruction in which students work together to achieve a learning goal and it gives affective results (Rahmawati, et al, 2023).…”
Section: Discussionsupporting
confidence: 61%
“…Minat adalah suatu preferensi dalam suatu kegiatan yang dilaksanakan melalui partisipasi aktif (Akma Adi Kasuma, 2017;Shavit et al, 2014). Oleh karena itu, minat penting untuk ditingkatkan karena minat belajar mempengaruhi hasil belajar (Yeh et al, 2019;Zhu & Kaiser, 2022). Beberapa ciri yang dapat diteliti jika siswa memiliki minat belajar matematika, yaitu lebih menyukai dan menyenangi belajar matematika daripada mata pelajaran lain, aktif dalam kegiatan baik di kelas maupun di luar kelas, lebih tertarik untuk memecahkan masalah matematika daripada matapelajaran lain, dan memiliki perhatian besar pada mata pelajaran matematika.…”
Section: Pendahuluanunclassified